Correction: Efficient singlet oxygen generation from sugar pendant C60 derivatives for photodynamic therapy. Issue 99 (20th November 2015) - Yano, Shigenobu; Naemura, Masami; Toshimitsu, Akio; Akiyama, Motofusa; Ikeda, Atsushi; Kikuchi, Jun-ichi; Shen, Xiande; Duan, Qian; Narumi, Atsushi; Inoue, Masahiro; Ohkubo, Kei; Fukuzumi, Shunichi
Abstract : Correction for 'Efficient singlet oxygen generation from sugar pendant C60 derivatives for photodynamic therapy' by Shigenobu Yano et al., Chem. Commun., 2015, DOI: ; Web:10.1039/c5cc07353g .